1993
DOI: 10.3109/10611869308996077
|View full text |Cite
|
Sign up to set email alerts
|

Passive Vectoring of a Colloidal Carrier System for Sodium Stibogluconate: Preparation, Characterization and Performance Evaluation

Abstract: The intracellular residence of the Leishmania parasite in the cells of the reticuloendothelial system--predominantly the liver and spleen--prompted the development of a polymeric, particulate, colloidal carrier system for the antileishmanial drug sodium stibogluconate. The system was pharmaceutically characterized for shape, size, structural integrity, electrokinetic properties and in vitro drug release. The relationship between such physical parameters as size, electrophoretic mobility and surface charge and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The mean size of a colloidal drug carrier is an important requisite that can influence the delivery device's biological effectiveness (26,42). In order to obtain liposome colloidal suspensions with a reduced mean size, the extrusion through polycarbonate filters was carried out.…”
Section: Resultsmentioning
confidence: 99%
“…The mean size of a colloidal drug carrier is an important requisite that can influence the delivery device's biological effectiveness (26,42). In order to obtain liposome colloidal suspensions with a reduced mean size, the extrusion through polycarbonate filters was carried out.…”
Section: Resultsmentioning
confidence: 99%
“…Parameters for in vitro characterization of different liposomal formulations include size, shape, size distribution, entrapment efficiency and in vitro drug release profile. It is earlier reported that mean size of a colloidal drug carrier is an important requisite that may influence the in vivo performance of delivery system [40]. In order to obtain liposome colloidal suspensions with a reduced mean size, the sonication with probe sonicator was carried out.…”
Section: Discussionmentioning
confidence: 99%
“…Parameters for in vitro characterization of different liposomal formulations include size, shape, size distribution, zeta potential, entrapment efficiency, and in vitro drug release profile. As reported previously, mean size and zeta potential of a colloidal drug carrier are important parameters that influence the in vivo performance of delivery systems (Karajgi et al 1993). In order to obtain liposome colloidal suspensions with a reduced mean size, sonication was carried out with a probe sonicator.…”
Section: Discussionmentioning
confidence: 99%